1995
DOI: 10.3354/meps119221
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and facilitatory effects of microbial films on settlement of Balanus amphitrite amphitrite larvae

Abstract: Larvae of the barnacle Balanus amphltr~te amphltrite Darwin (Crustacea Cirnpedia) respond to microbial surface film cues at settlement (l e attachment and metamorphosis) The effects of fllms of varylng ages on the settlement behavlour of B amphitrite cypnds were examined in laboratory cholce assays uslng substrata preconditioned In natural seawater for longer penods (up to 18 d ) than previous studies Furthermore, in this study only known numbers of cyprids (either 1 or 20 larvae) per film treatment were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
4
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 15 publications
5
53
4
1
Order By: Relevance
“…Biofilms have been intensively studied with respect to their stimulatory and inhibitory roles on larval attachment and metamorphosis of polychaetes (Lau & Qian 2001) and barnacles (Wieczorek et al 1995, Maki et al 1998, Olivier et al 2000. In this study, we extended previous investigations on larval settlement cues of the polychaete Hydroides elegans (Haswell).…”
Section: Introductionsupporting
confidence: 61%
“…Biofilms have been intensively studied with respect to their stimulatory and inhibitory roles on larval attachment and metamorphosis of polychaetes (Lau & Qian 2001) and barnacles (Wieczorek et al 1995, Maki et al 1998, Olivier et al 2000. In this study, we extended previous investigations on larval settlement cues of the polychaete Hydroides elegans (Haswell).…”
Section: Introductionsupporting
confidence: 61%
“…The impact of the bacterial component, which was not studied in the present study, is also known to have an effect on barnacle settlement (e.g. Strathmann et al 1981, Grosberg 1982, Wieczorek et al 1995. However, it is reasonable to believe that bacterial films probably CO-vary with microalgae.…”
Section: Selection Of Habitatcontrasting
confidence: 39%
“…Many decades of subsequent research have demonstrated that responses to bacterial films vary among different types of larvae (reviewed by Hadfield & Paul 2001). For example, larval settlement in Balanus amphitrite is inhibited by early, 1 to 3 d, natural biofilms, but is stimulated by 12 to 18 d films (Wieczorek et al 1995). By contrast, settlement intensity of Hydroides elegans correlates tightly with the density of bacterial cells in biofilms (Hadfield et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Selective settlement on biofilms has been shown for larvae of many marine invertebrates, including the scleractinian corals Acropora willisae and A. millepora (Negri et al 2001), the scyphomedusae Cassiopia spp. (Hofmann et al 1996), the polychaetes Janua brasiliensis (Kirchman et al 1982) and Pomatoceros lamarkii (Hamer et al 2001), the bryozoan Bugula neritina (Maki et al 1989), the oyster Crassostrea gigas (Fitt et al 1990), the sea scallop Placopecten magellanicus (Parsons et al 1993), the mussel Mytilus edulis (Satuito et al 1995), the barnacles Balanus amphitrite (Wieczorek et al 1995), Elminius modestus and Balanus perforatus (Neal & Yule 1994), the starfish Acanthaster planci (Johnson & Sutton 1994) and the ascidian Ciona intestinalis (Szewzyk et al 1991).…”
Section: Introductionmentioning
confidence: 99%